A co-design methodology based on model driven architecture for real time embedded systems - Lecomte, Stéphane; Guillouard, Samuel; Moy, Christophe; Leray, Pierre; Soulard, Philippe (Mathematical and computer modelling, 2011)
This paper presents the MOPCOM design methodology, developed to enable the efficient design of real time embedded systems, in particular radio (such as software defined radio) communication and video processing equipment. Based on UML and the model driven architecture approach, it could be advantageously applied for the design of a system on a chip or a system on a programmable chip. The MOPCOM methodology defines a set of rules for building UML models for embedded systems, from which Hardware Description Language code is automatically generated by means of a set of model transformations. The MARTE profile is used to describe real time properties and to perform platform modeling. A wireless communication demonstrator is presented to illustrate the methodology and the tooling.